Emotion in sales performance: affective orientation and need for cognition and the mediating role of motivation to work. Issue 1 (5th February 2018) - Nowlin, Edward; Walker, Doug; Deeter-Schmelz, Dawn R.; Haas, Alexander
Abstract : Purpose: The purpose of this paper is to investigate whether and under what condition does affective orientation (AO) drive salesperson performance (SP) and whether there is a tradeoff between affective orientation and the need for cognition (NFC). Using career stage theory, this research proposes that emotion is important and that the relationship between AO and SP is conditional and mediated. Design/methodology/approach: The hypothesized model is tested using survey data that were collected from 611 attendees at a Midwest regional sales meeting of a national direct selling organization. The model was estimated using 5, 000 bootstrapped samples drawn to assess the conditional and indirect effects. Findings: The findings reveal that AO increases SP when mediated through motivation to work (MW), but only during the salesperson's initial stage of their career – their first year. In subsequent career stages, AO's impact on SP diminishes, while NFC's impact on SP remains significant regardless of career stage. Research limitations/implications: The data were collected from a single selling organization. Practical implications: This study increases the understanding of the relationship between salesperson emotion (AO) and SP. This informs sales managers that new salespeople interpret information both emotionally and cognitively, which impacts the management of early career salespeople. Originality/value: Sales research rarely investigates the role of emotion. This research finds that emotion can be an asset to new salespeople. However, the need for emotion (AO) decreases with experience and no longer has a significant impact on performance after the initial stage.